(untitled) (Mwanga wa Lugha, 2024)
The objective of this paper is to analyze and evaluate the impact of slavery on the mapping and construction of self and gender identities in Mohamed S. Mohamed Kiu (1972) and Nyota ya Rehema (1976). The study will use a composite approach comprising New Historicism, Gender Criticism and Stylistics. New Historicism helped to situate and map the works analyzed in relation to particular Zanzibarian epochs. Gender criticism was expended in interrogating how women and men in feudal Zanzibarian society related with each other at all levels of social interaction and the impact on their self and gender identities. Finally, stylistics was used to interrogate and evaluate the dominant structural and stylistic features of the choice texts and their impact on the study topic. The study was guided by two hypotheses, viz, that in feudal Zanzibarian society, racialism and the dominant ideologies (patriarchy and Islam), impacted negatively on self and gender identities of both female and male members of society. Secondly, this study contends that, the stylistic devices used in each one of the choice texts, were important in delineating the mapping and construction of self and gender identities.